Evaluating the liquidity response of South African exchange-traded funds to country risk effects - Damien Kunjal (Economies, 2022)
Liquidity is important for the stability of financial markets and the growth of national economies. However, the liquidity of financial markets may be influenced by country risk shocks through informational asymmetry, funding constraints, and portfolio rebalancing activities. Therefore, the objective of this study is to investigate the effects of disaggregated country risk components on the liquidity of the South African Exchange-Traded Fund (ETF) market. The sample employed segregates South African ETFs based on their benchmarking styles - particularly, ETFs with domestic benchmarks and ETFs with international benchmarks. The results from the panel Autoregressive Distributed Lag (ARDL) model suggest that the liquidity of ETFs tracking domestic benchmarks is influenced positively by all country risk components in the long run, although only political and financial risks positively influence its short-run liquidity. Similarly, political and economic risk shocks positively influence the liquidity of ETFs tracking international benchmarks in the long-run; however, financial risk negatively influences its liquidity in both the long and short run. These findings suggest that investors can improve the overall performance and liquidity of their portfolios by taking into account the stability of political, financial, and economic risks.
Keywords: 330; economic risk; exchange-traded fund; financial risk; market return; political risk